2021
DOI: 10.1158/2159-8290.cd-20-0868
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Trial of the Oral Ataxia Telangiectasia and RAD3-Related (ATR) Inhibitor BAY 1895344 in Patients with Advanced Solid Tumors

Abstract: Targeting the ataxia telangiectasia and Rad3-related (ATR) enzyme represents a promising anticancer strategy for tumors with DNA damage response (DDR) defects and replication stress, including inactivation of ataxia telangiectasia mutated (ATM) signaling. We report the dose-escalation portion of the phase I first-inhuman trial of oral ATR inhibitor BAY 1895344 intermittently dosed 5-80 mg twice daily (BID) in 21 patients with advanced solid tumors. The maximum tolerated dose was 40 mg BID 3 days on/4 days off.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(170 citation statements)
references
References 28 publications
9
160
0
1
Order By: Relevance
“…However, in the other three cases killing was supra-additive since these cells were relatively resistant to either Ara-C or VE821, yet still manifested >95% killing in the presence of the combination. These results were confirmed using a second, more potent ATR inhibitor BAY-1895344, which is also in clinical trials (61)…”
Section: Collectively the Data Argue Against Selective Enrichment Formentioning
confidence: 64%
“…However, in the other three cases killing was supra-additive since these cells were relatively resistant to either Ara-C or VE821, yet still manifested >95% killing in the presence of the combination. These results were confirmed using a second, more potent ATR inhibitor BAY-1895344, which is also in clinical trials (61)…”
Section: Collectively the Data Argue Against Selective Enrichment Formentioning
confidence: 64%
“…ATR inhibition has been shown to be synthetically lethal with ATM deficiency in preclinical models, translating to responses to monotherapies that have been reported with agents such as BAY1895344 and M6620. 25 , 36 The complete loss of ATM protein is ideally confirmed by protein immunohistochemistry, but this is not yet a standard laboratory test. Genetic testing is not as certain, although LOH can sometimes be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…ATM deficiency is expected to sensitize malignant cells to ATR inhibition, which has been demonstrated both in preclinical models and in clinical trials. [22][23][24][25] Additionally, in preclinical pancreatic and lung cancer models, ATM deficiency also sensitizes to PARP inhibition, suggesting that combined ATR and PARP inhibition may be useful. 26,27 In contrast, other studies showed low sensitivity of ATMdeficient prostate cancers to PARP inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing replicative damage by blunting the RepStress response pathways with ATR inhibitors is discussed below [8,[63][64][65][66][67]. Synthetic lethality for the PARP inhibitors and platinum derivatives in HRD cancers is being applied for cancer treatment [68,69] and recent studies in animal models suggest such synthetic lethality for TOP1 inhibitors [10,58].…”
Section: Repstress Induced By Clinically Approved Chemotherapeutic Agentsmentioning
confidence: 99%